1999
DOI: 10.1046/j.1464-410x.1999.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline and nitrite‐nitrate concentrations in the contralateral testes during ipsilateral spermatic cord torsion in the presence or absence of a testis and epididymis

Abstract: Objective To determine the changes occurring during diCerences in content between groups 1 and 3, 1 and 4, and 2 and 4. The content in group 4 was ipsilateral spermatic cord torsion either in the presence or absence of the ipsilateral testis and epididymis, by significantly less than that in group 3. There were no significant diCerences in nitrite-nitrate contents evaluating noradrenaline and nitrite-nitrate concentrations in the contralateral testes.among any of the groups. Conclusion Spermatic cord torsion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is also reported that CGRP may regulate the electrolyte and fluid secretion in the epididymis, thereby providing an optimal microenvironment for the maturation and storage of the spermatozoa [27]. CGRP further inhibits the release of norepinephrine [28]which was previously reported to be released in excessive amounts in contralateral testis during unilateral testicular torsion [29]. The administration of capsaicin may have further released CGRP and caused dilatation of the vessels thus contributed to the preservation of blood flow to the contralateral testis.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that CGRP may regulate the electrolyte and fluid secretion in the epididymis, thereby providing an optimal microenvironment for the maturation and storage of the spermatozoa [27]. CGRP further inhibits the release of norepinephrine [28]which was previously reported to be released in excessive amounts in contralateral testis during unilateral testicular torsion [29]. The administration of capsaicin may have further released CGRP and caused dilatation of the vessels thus contributed to the preservation of blood flow to the contralateral testis.…”
Section: Discussionmentioning
confidence: 99%
“…Auto‐immunization was proposed as the mechanism of contralateral testicular injury [2], but increased levels of tissue hypoxia products such as lactic acid and hypoxanthine suggest a reflexive decrease in contralateral testicular blood flow by a neurovascular stimulus triggered by an ipsilateral testicular injury [3,4]. Currently the probable mechanism of contralateral injury is accepted as a vasospasm through a sympathetic reflex arc, and hypoxia may be the reason for contralateral injury after unilateral testicular obstruction [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most popular theory proposed to explain the contralateral testicular damage has been the autoimmune response [18] . But the deterioration of the contralateral testis within 24 h of spermatic cord torsion, even in the absence of ipsilateral testis and epididymis makes the role of autoimmunity obscure [19][20][21] . Experimental models of unilateral testicular damage have resulted in decreased blood flow and an increase in the biochemical indicators of tissue hypoxia within the contralateral testis [20][21][22][23][24][25][26] , and the sympathetic nervous system is activated by exposure to noradrenaline in the contralateral testis during ipsilateral spermatic cord torsion [21] .…”
Section: Discussionmentioning
confidence: 99%
“…But the deterioration of the contralateral testis within 24 h of spermatic cord torsion, even in the absence of ipsilateral testis and epididymis makes the role of autoimmunity obscure [19][20][21] . Experimental models of unilateral testicular damage have resulted in decreased blood flow and an increase in the biochemical indicators of tissue hypoxia within the contralateral testis [20][21][22][23][24][25][26] , and the sympathetic nervous system is activated by exposure to noradrenaline in the contralateral testis during ipsilateral spermatic cord torsion [21] . It is suggested that oxidative and antioxidative systems can be activated by the pathway of contralateral testicular deterioration [17][18][19][20][21][22][23][24][25][26] , and this study can also help explain how epididymitis affects the contralateral testis, and why unilateral infection causes infertility.…”
Section: Discussionmentioning
confidence: 99%